Psychological Risk Factors for Healthcare Professionals in the Epidemic Process - Perihan Eren Bana (ACHSM, 2020)
In this study, it is aimed to reveal the increased psychological risk factors for the healthcare professionals who perform their duties with great devotion during the epidemic process. This article, which was prepared by making use of the studies in the literature, aimed to examine the factors that prepare increased stress and burnout during the epidemic process. It is seen that the factors that cause burnout and depersonalization among healthcare workers in the process of providing health services, increase in the epidemic process and gain new dimensions. Especially risk factors faced by emergency personnel are always considered as a professional risk factor in daily operation, but the negative emotions and thoughts caused by daily functioning in the epidemic process increase much more. In this context, the importance of increasing the psychological resilience of healthcare professionals and supporting them psycho-socially is increasing. Providing these supports during and after the epidemic is also important in terms of maintaining quality in health care. It is considered that the provision of mental health professionals who will provide continuous support for healthcare professionals in the institution should be among the mandatory occupational health and safety measures.